Excuse me : the survival guide to modern business etiquette - Thomas, Rosanne J. (AMACOM, American Management Association, 2017)
Exactly what are the rules these days? Is it acceptable to text your boss at home? What is the polite way to ask a colleague to take a distracting conversation behind closed doors? What about the use of smartphones in meetings? Merging classic rules of behavior with new realities of modern business, Excuse Me spotlights dozens of puzzling situations, with suggestions for bridging generational and cultural divides.